Innovación y progreso técnico: teoría y política tecnológica; una referencia al caso colombiano (1990)
The economic literature on innovation and technological progress is not very abundant and only recently has been gaining importance in studies related toproblems of development. In Colombia, some objectives of technical renewal in productive processes has been included in development policies but these goals have not been reached yet due to various factors. So, it is necessary to undertake serious research to analyze these factors and lo formulate new policies for scientific and technological development of Colombia: In the essay, the author re-examine the theories on this topic as well as the treatment given to the problem of scientific and technological development in economic development programs in Colombia, during recent years.